2017
DOI: 10.1111/jgh.13797
|View full text |Cite
|
Sign up to set email alerts
|

miR‐200b‐containing microvesicles attenuate experimental colitis associated intestinal fibrosis by inhibiting epithelial‐mesenchymal transition

Abstract: miR-200b could be transferred from genetically modified BMSCs to the target cells or tissue by MVs. The mechanisms of miR-200b-MVs in inhibiting colonic fibrosis were related to suppressing the development of EMT by targeting ZEB1and ZEB2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 39 publications
1
43
0
1
Order By: Relevance
“…Bone marrow mesenchymal stem cells (BMSCs) transfected with lentivirus to overexpress miR-200b can release EVs packaged with miRNA-200b. The miR-200b-EVs significantly suppressed ZEB1 and ZEB2 to reverse the morphology in TGF-β1-treated IEC-6 cells and ameliorate the TNBS-(2,4,6-trinitrobenzene sulfonic acid-) induced colon fibrosis histologically [129]. EVs secreted by mesenchymal stromal cells (MSCs) have been proposed as important mechanistic relievers in response to cellular inflammation through paracrine effects [130][131][132].…”
Section: The Clinical Potential Of Evs On Treatmentmentioning
confidence: 99%
“…Bone marrow mesenchymal stem cells (BMSCs) transfected with lentivirus to overexpress miR-200b can release EVs packaged with miRNA-200b. The miR-200b-EVs significantly suppressed ZEB1 and ZEB2 to reverse the morphology in TGF-β1-treated IEC-6 cells and ameliorate the TNBS-(2,4,6-trinitrobenzene sulfonic acid-) induced colon fibrosis histologically [129]. EVs secreted by mesenchymal stromal cells (MSCs) have been proposed as important mechanistic relievers in response to cellular inflammation through paracrine effects [130][131][132].…”
Section: The Clinical Potential Of Evs On Treatmentmentioning
confidence: 99%
“…If this mechanism was supported by further studies, potential therapeutic strategies may involve miRNA manipulation. For example, recent work has demonstrated that microvesicle‐delivered miR‐200b reduces colonic fibrosis in TNBS‐induced experimental colitis . Furthermore, preclinical trials that assess the therapeutic impact of targeting miRNAs have already begun .…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent work has demonstrated that microvesicle-delivered miR-200b reduces colonic fibrosis in TNBS-induced experimental colitis. 45 Furthermore, preclinical trials that assess the therapeutic impact of targeting miRNAs have already begun. 46,47 Limitations to therapeutic use of miRNA modulation, include off-target effects [48][49][50]…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, BMSCs were infected with a miRNA-200b-expressing lentivirus, and MVs were isolated through a differential centrifugation method. The collected MVs were subsequently used to treat TNBS-induced rat intestinal fibrosis [107]. Zhang et al demonstrated the suppressive effect of MVs containing miRNA-29a/c on tumor growth in gastric cancer (GC) [108].…”
Section: Cell-derived Membrane Vesiclesmentioning
confidence: 99%